2022
DOI: 10.3390/ijerph191811749
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Autopsy as a Tool for Defining Causes of Death in Specific Healthcare Contexts: Study of Applicability through a Traditional Literature Review

Abstract: Autopsy examination, the gold standard for defining causes of death, is often difficult to apply in certain health care settings, especially in developing countries. The COVID-19 pandemic and its associated difficulties in terms of implementing autopsy examinations have made the need for alternative means of determining causes of death even more evident. One of the most interesting alternatives to the conventional autopsy is the verbal autopsy, a tool that originated in Africa and Asia in the 1950s and consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Most studies evaluating the VA questionnaire, however, have not been validated against the gold standard (conventional diagnostic autopsy), which typically involves medical record interpretation 22 . Therefore, we aimed to define the sensitivity and specificity of the VA questionnaire in situations in which conventional autopsies cannot be performed due to biosafety issues or excess deaths at home without medical assistance 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies evaluating the VA questionnaire, however, have not been validated against the gold standard (conventional diagnostic autopsy), which typically involves medical record interpretation 22 . Therefore, we aimed to define the sensitivity and specificity of the VA questionnaire in situations in which conventional autopsies cannot be performed due to biosafety issues or excess deaths at home without medical assistance 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Validation studies comparing VA assigned causes of death to hospital records have shown mixed results [ 15 , 16 , 43 ]. Therefore, though deaths assigned using VA are important in settings with weak systems for registering and determing causes of death, they should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Using death certificates, some surveillance teams have identified drug overdose deaths from cause of death fields available before the final cause of death coding [13][14][15]. Other teams have used text from verbal autopsies, which describe interviews with witnesses or relatives, as opposed to forensic autopsies, which detail findings from extensive physical examinations and toxicology tests [16,17]. Text from forensic autopsy reports has been used for the automatic classification of causes of death unrelated to drug overdoses [18].…”
Section: Introductionmentioning
confidence: 99%